2014
DOI: 10.1055/s-0034-1383181
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Total Steroid Saponins from Dioscorea zingiberensis against Transient Focal Cerebral Ischemia-Reperfusion Injury in Rats via Anti-Inflammatory and Antiapoptotic Effects

Abstract: Total steroid saponins isolated from Dioscorea zingiberensis have shown a variety of beneficial bioactivities. However, there are no reports about their neuroprotective effects, until now. Therefore, in the present study, we explored the neuroprotective effects of the total steroid saponins from D. zingiberensis on rats against transient focal cerebral ischemia-reperfusion and their underlying mechanisms. Healthy adult Sprague-Dawley rats were randomly assigned to six groups. After pretreatment with D. zingibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, we found that, compared with WT group, the number of Nissl bodies in neurons of WT BTI model group decreased obviously (Fig. 7g, h, P < 0.05), which was consistent with previous literature [45]. Most importantly, compared with WT BTI model, the number of Nissl bodies in neurons decreased obviously in miR-7 def BTI Fig.…”
Section: Rorα and Mir-7 Are Co-expressed In Neurons In Bti Modelsupporting
confidence: 91%
“…However, we found that, compared with WT group, the number of Nissl bodies in neurons of WT BTI model group decreased obviously (Fig. 7g, h, P < 0.05), which was consistent with previous literature [45]. Most importantly, compared with WT BTI model, the number of Nissl bodies in neurons decreased obviously in miR-7 def BTI Fig.…”
Section: Rorα and Mir-7 Are Co-expressed In Neurons In Bti Modelsupporting
confidence: 91%
“…Thus, CEE may potentially elicit neuroprotection by promoting axonal regeneration. There is increased survival of Nissl bodies after treatment with the neuroprotective agents borneol and ligustrazine and Dioscorea zingiberensis steroid saponins (Zhang et al, 2014; Yu et al, 2016). This finding seems to be closely related to our previous data, which indicated that protosappanin B (Zeng et al, 2015a), one of the major neuroprotective compounds in CEE, significantly increases the expression of the neurosynaptic markers GAP43 and MAP-2 in PC12 cells and primary neurons (Behravan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, together with its promising therapeutic effects, toxicological investigation of TCM on experimental animals is indispensable to provide for an appropriate dosage selection for its clinical use. In recent years, D. zingiberensis , an ethno pharmacological and traditional TCM, has demonstrated to exert some newly emerging bioactivities as afore-mentioned in the “ introduction section ” and triggered our interest to explore its chemical composition for pharmacological and clinical applications in depth with extensive efforts [1012]. The essential TSSN extracts originated from D. zingiberensis have been elaborated as the bioactive compounds that are attributable to the observable effects according to our previous chemical and pharmacological investigations which provided the concentration of some biomarker constituents [17, 21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Several phytochemical investigations have revealed the variety of constituents comprising the matrix of extracted samples of D. zingiberensis and total steroid saponins (TSSN) mainly presenting in spirostan and furostan forms makes the largest portion of the constituents. Extracts of TSSN from this plant have demonstrated the signals that TSSN can be the potential bioactive ingredients for the treatment of various diseases, for example cough, anthrax, rheumarthritis, tumefaction, sprain, cerebrovascular as well as cardiac diseases [1012]. …”
Section: Introductionmentioning
confidence: 99%